URGENSI KOMPILASI HUKUM ISLAM (KHI) DAN METODE IJTIHAD DALAM MENGHADAPI PERKEMBANGAN HUKUM ISLAM DI INDONESIA - Rachmat Syafe’i (Asy-Syari'ah, 2015)
The tradition of Islamic law in Indonesia's Muslim population can not be separated from values, legal norms, and legal products. Therefore, the position of ijtihad is one of the important instruments in Islam. In this context, a mujtahid in general perform several steps in formulating Islamic rules from the sources, that are the Quran and Hadith. The position of Islamic law in the legal system in Indonesia is increasingly gaining recognition juridically. One of that is  enactment of the Marriage Law Number 1 Year 1974 and Presidential Decree Number 1 Year 1991 on the Compilation of Islamic Law. Thus the actualization of Islamic law must be carried out systematically by concrete actions. Actualization of Islamic law is not enough, it will even harm if done only for political action which campaign demanding the implementation of Shari'a. One of the problems encountered in attempts to actualize Islamic law is the absence of a clear conception of the legal matter that must be actualized in national law, both of which apply specifically to Muslims and generally applicable.